Defective Toll-Like Receptors Driven B Cell Response in Hyper IgE Syndrome Patients With STAT3 Mutations - Gong, Ruolan; Wu, Jing; Jin, Yingying; Chen, Tongxin (Frontiers in Pediatrics, 2021)
Autosomal dominant hyper-IgE syndrome (AD-HIES) is a rare inherited primary immunodeficient disease, which is caused by STAT3 gene mutations. Previous studies indicated a defective Toll-like receptor (TLR) 9-induced B cell response in AD-HIES patients, including proliferation, and IgG production. However, the other TLRs-mediated B cell responses in AD-HIES patients were not fully elucidated. In this study, we systematically studied the B cell response to TLRs signaling pathways in AD-HIES patients, including proliferation, activation, apoptosis, cytokine, and immunoglobulin production. Our results showed that the TLRs induced B cell proliferation and activation was significantly impaired in AD-HIES patients. Besides, AD-HIES patients had defects in TLRs-induced B cell class switch, as well as IgG/IgM secretion and IL-10 production in B cells. Taken together, we first systematically reported the deficiency of TLRs driven B cell response in AD-HIES patients, which help to have a better understanding of the pathology of AD-HIES.